Developing student character through disciplinary curricula: an analysis of UK QAA subject benchmark statements. Issue 6 (2nd June 2016) - Quinlan, Kathleen M.
Abstract : What aspects of student character are expected to be developed through disciplinary curricula? This paper examines the UK written curriculum through an analysis of the Quality Assurance Agency's subject benchmark statements for the most popular subjects studied in the UK. It explores the language, principles and intended outcomes that suggest students are expected to embrace or embody particular affective outcomes, values or virtues, or demonstrate social responsibility. The statements emphasise cognitive/intellectual skills, with little attention to the development of personal virtues or values. However, when present, the richest expressions are embedded in the values of the particular discipline, rather than presented as 'transferable skills'. The paper presents three examples of virtues that underpin particular disciplines, including empathy as expressed in languages and related studies and art and design; social justice and courage as expressed in social work; and humility as expressed in biosciences and sociology. Implications for higher education policy are suggested.